2018
DOI: 10.1002/zaac.201800370
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Li(TFSI)@Polyethylene Oxide Membranes as Solid Electrolytes

Abstract: Thin membranes of lithium‐bis(trifluoromethan)sulfonimide@poly (ethylene oxide) (or Li(TFSI)@PEO) were fabricated by electrospinning from acetonitrile solutions of the starting materials at room temperature. Membranes were tested with and without succinonitrile (SN), acting as a plasticizer to enhance the ion mobility in the systems. Our experiments substantiate, that SN does influence the electrochemical performance and physical properties of the membranes. Homogeneous amorphous membranes were only realized f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…reported an electrospinning procedure as an efficient and facile method for the fabrication of all‐solid‐state nanofibrous electrolytes applicable in LIBs. In 2018, Walke et al . also demonstrated the highest ionic conductivity of 0.28 mS cm −1 for an electrospun PEO/LiTFSI electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…reported an electrospinning procedure as an efficient and facile method for the fabrication of all‐solid‐state nanofibrous electrolytes applicable in LIBs. In 2018, Walke et al . also demonstrated the highest ionic conductivity of 0.28 mS cm −1 for an electrospun PEO/LiTFSI electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Presence of a more amorphous region is confirmed due to the appearance of the smooth surface of nanofibers, which fulfill the aim of a flexible and rigid polymer electrolyte, solely responsible for the conduction of ions independently in the polymer electrolyte. 44,45 The outer surface of the membrane is accumulated by the LLBZO nanoparticle as well as an electrolyte in which these membranes are soaked for 24 h. The soaked membranes were dried for 6 h to get the all-solidstate esHPME. Figure S1 shows the SEM images of 5 and 15 wt % LLBZO-incorporated PVDF-HFP.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the existence of the small pores in the electrospun structures facilitates the mobility and migration of the Li + ions. Hence, the electrospun membranes provide higher ionic conductivities compared with the solution‐casted ones 24‐26 . Previous studies clearly showed the effect of inert oxide fillers (including SiO 2 , Al 2 O 3 , TiO 2, and ZnO) on the ionic conductivity enhancement of the electrospun PEO‐based membranes 27,28 .…”
Section: Introductionmentioning
confidence: 93%
“…Hence, the electrospun membranes provide higher ionic conductivities compared with the solution-casted ones. [24][25][26] Previous studies clearly showed the effect of inert oxide fillers (including SiO 2 , Al 2 O 3 , TiO 2, and ZnO) on the ionic conductivity enhancement of the electrospun PEO-based membranes. 27,28 According to the obtained results, the highest ionic conductivity of 0.087 mS.cm −1 could be obtained by insertion of SiO 2 nanofillers into the PEO-based electrospun fibers.…”
Section: Introductionmentioning
confidence: 99%